Relationship between Speech Perception and Level of Satisfaction of Hearing Aid Users - Mantello, Erika Barioni; Silva, Carla Dias da; Massuda, Eduardo Tanaka; Hyppolito, Miguel Angelo; Reis, Ana Cláudia Mirândola Barbosa dos (International Archives of Otorhinolaryngology, 2016)
Introduction Hearing difficulties can be minimized by the use of hearing aids.Objective The objective of this study is to assess the speech perception and satisfaction of hearing aids users before and after aid adaptation and to determine whether these measures are correlated.Methods The study was conducted on 65 individuals, 54% females and 46% males aged 63 years on average, after the systematic use of hearing aids for at least three months. We characterized subjectś personal identification data, the degree, and configuration of hearing loss, as well as aspects related to adaptation. We then applied a satisfaction questionnaire and a speech perception test (words and sentences), with and without the use of the hearing aids.Results Mean speech recognition with words and sentences was 69% and 79%, respectively, with hearing aids use; whereas, without hearing aids use the figures were 43% and 53%. Mean questionnaire score was 30.1 points. Regarding hearing loss characteristics, 78.5% of the subjects had a sensorineural loss, 20% a mixed loss, and 1.5% a conductive loss. Hearing loss of moderate degree was present in 60.5% of cases, loss of descending configuration in 47%, and plain loss in 37.5%. There was no correlation between individual satisfaction and the percentages of the speech perception tests applied.Conclusion Word and sentence recognition was significantly better with the use of the hearing aids. The users showed a high degree of satisfaction. In the present study, there was no correlation observed between the levels of speech perception and levels of user satisfaction measured with the questionnaire.
Keywords: hearing perception; patient satisfaction; hearing loss; hearing aids; questionnaires